Driving Simulator Study for Evaluating the Effectiveness of Virtual Warnings to Improve the Safety of Interaction Between Cyclists and Vehicles. Issue 4 (April 2022) - Calvi, Alessandro; D'Amico, Fabrizio; Ferrante, Chiara; Bianchini Ciampoli, Luca
Globally, cyclists account for 3% of all road traffic deaths, with the highest percentage occurring in Europe (8%) where the bicycle is considered a true alternative mode of transport. Among the causes of crashes are vehicles overtaking cyclists, especially on rural roads. In this study, a new application of augmented reality (AR) warnings for connected vehicles is tested by means of a driving simulator. The overall objective of the study consists in assessing the effectiveness of three proposed AR systems in improving the safety of interactions between vehicles and cyclists, especially during overtaking maneuvers. The AR systems were tested on a sample of 46 drivers and provided them with additional virtual visual information aimed at improving the driver's risk perception and assessment of safe distance from a cyclist. The virtual warning configurations were: (i) a yellow safety zone around the cyclist; (ii) a color-changing safety zone that changes from red to green when the driver has safe lateral space to overtake the cyclist; (iii) the same color-changing security zone but with an additional acoustic warning. The AR warnings were found to be quite effective as they helped drivers overtake cyclists more safely. With AR warnings (especially with the additional audio), it was found that drivers adopted longer distances from cyclists and entered the oncoming lane less frequently, thus lowering the risk of collision with cyclists as well as the risk of head-on collision with oncoming vehicles.